THE DIFFERENCE IN LEARNING OUTCOMES OF CLASS V STUDENTS BEFORE AND AFTER COVID-19 AT PUBLIC ELEMENTARY SCHOOL 095256 PEMATANG BANDAR - Aulia Nanda, Ficha; Uribe, Martin; O Tambunan, Jubelando; Jusnita Samosir, Herna; Nur Asima Sidabutar, Melisa (Universitas Efarina, 2020)
AbstractThis research was motivated by seeing student learning outcomes during the pandemic that had increased compared to learning outcomes before Covid-19 which was seen from the list of odd and even semester test scores for the 2019/2020 academic year at SD Negeri 095256 Pematang Bandar. The objectives of this study are (1) How Student Learning Outcomes before Covid-19 at SD Negeri 095256 Pematang Bandar; (2) What are the student learning outcomes during the covid-19 period at SD Negeri 095256 Pematang Bandar; (3) How are the differences in student learning outcomes before and after covid-19 in SD Negeri 095256 Pematang Bandar. This research is a type of quantitative research type of experiment. The sample used in this study were 27 students and the population used was all class V SD Negeri 095256 Pematang Bandar. Based on the results of the research data analysis, the test scores in this odd semester have a Liliefors value (L0 = 0.1694 > Lt = 0.173). The results of the test scores in this even semester have a Liliefors value (L0 = 0.14563 > Lt = 0.173). While the results of the homogeneity test using the F-test were obtained (Fcount < Ftable = 1.474 < 1.674). While the results of hypothesis testing using the t-test were obtained (tcount = 2.76 > ttable = 2.012). So it can be concluded that there is a significant difference between student learning outcomes before and after Covid-19 as seen from the List of T.P. Odd and Even Semester Exam Values. 2019/2020 In the Country 095256 Pematang Bandar.